The Influence of Providing Leaflet Media Education on the Level of Knowledge, Attitudes, and Behavior Regarding Dengue Fever in the Population of Kromengan District - Marindra Firmansyah; Muhammad Ilham Bagas Waskito; Annur Affin Niswah; Nurbella Sannyngtyas; Salsa Bella Firdausy Intania; Dewi Aminah Yuni Rosafiana (PT FORMOSA CENDEKIA GLOBAL, 2025)
The incidence of dengue hemorrhagic fever in Kromengan Subdistrict increased from 24 cases in 2023 to 80 cases in 2024. This is supported by increased rainfall at the end of 2024. The proposed innovative program is Weber (Weekend Bersih) which is consistently carried out by the entire community on Saturdays in the morning to increase public awareness in carrying out the PSN 3M plus. The promotion of health in the form of socialization GERTAK NYAMUK (Gerakan Serentak Taklukan Nyamuk) is intended to increase awareness of the level of knowledge, attitudes and behavior about dengue fever. The results of data recapture show that dengue hemorrhagic fever has increased significantly. The result of problem prioritization using the USG method is dengue hemorrhagic fever. Health promotion in the form of counseling using leaflets and educational videos. This activity was carried out in the community as many as 120 people from Ngadirejo Village and Peniwen Village. The results showed that providing leaflet media education can increase the level of knowledge, attitudes and behaviors related to dengue fever in the intervention group of Kromengan District residents. There is no significant difference in the level of knowledge, attitudes and behaviors related to dengue fever in the monitoring group of the Kromengan District Community.